Backcasting frugally innovative smart sustainable future cities - Ebolor, Alexander (Journal of Cleaner Production, 2023)
This paper envisions alternative scenarios for future cities that are resilient environmentally, socially, economically, and embedded in smart infrastructure and governance. It reinforces the position that although complementary, the backcasting approach is more appropriate for future city planning. There is limited research that envisions how future cities can be backcasted with frugal innovation (FI) underpinning the sustainability pillars. This research aims to narrow the gap. The methodology is based on a systematic literature review and secondary exploratory case studies. The results of the TOWS (threats, opportunities, weaknesses, strengths) analysis on the suitability of FI on smart sustainable cities (SSC) developmental policies show that FI is an affordable and inclusive way to sustainably develop cities without injury to the environment. The findings reveal that the five pillars of a smart sustainable future city can integrate frugal innovation and lean engineering concepts to ensure sustainable development at lower costs. Through frugal innovation embedded in city infrastructure, cleaner methods of production can be realized, and inclusiveness can be fostered.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Backcasting; ESG; Frugal innovation; SDGs; Smart sustainable cities; Inklusion